PENGARUH PEMBERIAN EKSTRAK ETANOL KULIT BUAH MANGGIS (Garcinia mangostana, L.) TERHADAP PENURUNAN KADAR LOGAM MERKURI PADA GINJAL MENCIT GALUR SWISS WEBSTER - Nela Simanjuntak; Marwatul Zamil; Tiara Berliani; Nur Asni Setiani (Sekolah Tinggi Farmasi Indonesia, 2021)
Mangosteen (Garcinia mangostana L.) is known as a plant rich in antioxidants and has various pharmacological activities. This study aims to determine the activity of the ethanolic extract of G. mangostana L. to decrease mercury levels in the kidneys. Mangosteen rind was extracted using 96% ethanol using the maceration method to form a thick extract. The experimental animals used in this study were Swiss Webster strain mice which were grouped into normal group (CMC suspension 0.5%), negative control (induction of HgCl2 solution), positive control (induction of HgCl2 solution followed by administration of curcumin at a dose of 100mg/KgBW). , and the test group was given mangosteen peel extract at a dose of 200mg/kgBW, 400mg/kgBW, 600mg/kgBW. In the test group, mice were induced using HgCl2 for 14 days, followed by administration of ethanol extract of mangosteen rind for 24 days. Observations were made with kidney organ surgery and observations were made using Atomic Absorption Spectrophotometry (AAS) and analyzed using ANOVA. The test results showed mercury accumulation in the negative, positive control group, and the test doses of 200, 400 and 600mg/kgBW, respectively, were 44.3mg/kg, 7.3mg/kg, 36.46mg/kg, 35.7mg/kg. kg and 31.34mg/kgBW with an effective dose of 600mg/KgBW.